Vanadium complexes with thiosemicarbazones: Synthesis, characterization, crystal structures and anti-Mycobacterium tuberculosis activity - Maia, Pedro I. da S.; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Lemos, Sebastiao S.; de Sousa, Gerimario F.; Batista, Alzir A.; Nascimento, Otaciro R.; Ellena, Javier; Castellano, Eduardo E.; Niquet, Elke; Deflon, Victor M. (Pergamon-Elsevier B.V. Ltd, 2009)
The development of more efficient anti-tuberculosis drugs is of interest. Three oxovanadium(IV) and three cis-dioxovanadium(V) complexes with thiosemicarbazone derivatives bearing moieties with different lipophilicity have been prepared and had their inhibitory activity against Mycobacterium tuberculosis H(37)Rv ATCC 27294 evaluated. The analytical methods used by the complexes' characterization included IR, EPR, (1)H, (13)C and (51)V NMR spectroscopies, elemental analysis, cyclic voltammetry, magnetic susceptibility measurement and single crystal X-ray diffractometry. [VO(acac)(aptsc)], [VO(acac)(apmtsc)] and [VO(acac)(apptsc)] (acac = acetylacetonate; Haptsc = 2-acetylpyridinethiosemicarbazone; Hapmtsc = 2-acetylpyridine-N(4)-methyl-thiosemicarbazone and Happtsc = 2-acetylpyridine-N(4)-phenyl-thiosemicarbazone) are paramagnetic and their EPR spectra are consistent with the monoanionic N,N,S-tridentate coordination of the thiosemicarbazone ligands, resulting in octahedral structures of rhombic symmetry and with the oxidation state +IV for the vanadium atom. As result of oxidation of the vanadium(IV) complexes above, the diamagnetic cis-dioxovanadium(V) complexes [VO(2)(aptsc)[, [VO(2)(apmtsc)[ and [VO(2)(apptsc)] are formed. Their (1)H, (13)C and (51)V NMR spectra were acquired and support a distorted square pyramidal geometry for them, in accord with the solid state X-ray structures determined for [VO(2)(aptsc)] and [VO(2)(apmtsc)]. In general, the vanadium compounds show comparable or larger anti-M. tuberculosis activities than the free thiosemicarbazone ligands, with MIC values within 62.5-1.56 (mu g/mL). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Oxovanadium(IV); Dioxovanadium(V); Thiosemicarbazones; Anti-Mycobacterium tuberculosis activity